SOSIALISASI PEMBUATAN PUPUK KOMPOS DI DESA PIJOT UTARA, LOMBOK TIMUR - Salman, Salman; Akbar, Zaenul; sultan, Sultan; sinarep, Sinarep; Salsananda, Dixie; Suksmadana, I Made Budi; Satiawan, I Nyoman Wahyu (Jurnal Bakti Nusa, 2025)
North Pijot Village, East Lombok has a problem with utilizing the organic waste, especially goat manure that has not been optimally utilized and has the potential to pollute the environment. The village community empowerment activity from the University of Mataram aims to overcome this problem by educating the community about the use of organic waste as a material for making compost. The activity methods include identifying problems, socialization and counseling, monitoring, filtering, harvesting/packaging. The results of the activity show that the North Pijot Village community has a better understanding of organic waste management and is able to spread composting techniques independently. This program not only contributes to reducing environmental pollution but also increases soil fertility and agricultural productivity. The sustainability of this program is expected to improve community welfare through more effective utilization of local resources.